An Unusual Case of BSND Gene–Related (Type IV) Bartter Syndrome Presenting as Antenatal Bartter Syndrome: A Case Report and Review of Literature. Issue 2 (26th April 2023) - Shajan, Aleena M.; Kumar, Manish; Navaneethan, Preethi; Danda, Sumita; Beck, Manisha M.
Abstract: Bartter syndrome is a group of autosomal recessive renal tubular disorders; it has two types of presentation: antenatal and classic. The antenatal type presents as severe unexplained polyhydramnios in the second trimester. This is due to fetal urinary losses of sodium, chloride, and potassium, leading to fetal polyuria. The classic type presents in the late neonatal or infancy stage, with dehydration, dyselectrolytemia, failure to thrive, and nephrocalcinosis. Antenatal scans are normal in such cases. Type I and II Bartter syndrome presents in the antenatal period, whereas type IV has a classic presentation. We describe an unusual case of type IVa Bartter syndrome presenting in the antenatal period, with severe polyhydramnios. The initial diagnosis was made based on amniotic fluid chloride levels and later confirmed by performing a genetic test. Genetic testing is important for confirming diagnosis and prognostication regarding the condition.